How the Allocation of Children’s Time Affects Cognitive and Noncognitive Development - Fiorini, Mario; Keane, Michael P. (Journal of Labor Economics, 2014)
The allocation of children’s time among different activities may be important for cognitive and noncognitive development. Here, we exploit time use diaries from the Longitudinal Study of Australian Children to study the effects of time allocation. By doing so, we characterize the trade-off between different activities to which a child is exposed. On the one hand, our results suggest that time spent in educational activities, particularly with parents, is the most productive input for cognitive skill development. On the other hand, noncognitive skills appear insensitive to alternative time allocations. Instead, they are greatly affected by the mother’s parenting style.